Pathological drivers of coral diseases across the Arabian Peninsula - Thierry M. Work; Greta S. Aeby; David Abrego; Jessica Bouwmeester; Emily Howells; Pedro Range; Maren Ziegler; Thor Jensen; Amanda Shore; Grace Vaughan; John A. Burt; Christian R. Voolstra; et al. (Coral Reefs, 2026)
Increasing trends of coral mortality are a challenge to coral reef management worldwide, and a need exists to identify the causes and pathways involved. Pathology is useful to help decipher potential causes of mortality in animals, because it illuminates agents associated with lesions and gives insights on the nature of how a host responds to said agents. To better understand the nature of threats facing corals in the Arabian Peninsula, we performed gross and microscopic pathology on corals from Saudi Arabia, Qatar, and the United Arab Emirates. Among 321 coral fragments examined from 21 genera, tissue loss was the most common lesion seen in 31% of samples, reflecting its widespread presence on reefs from the Arabian Peninsula. Histologically, 68% of lesions exhibited necrosis, predominantly in the basal body wall and surface body wall. Endolithic filamentous microalgae and sponges, originating from the skeleton, were associated with 57% and 39% of lesions, respectively, and were often linked to necrosis and hyaline membrane formation. Cell-associated microbial aggregates and coccidia were detected mainly in Acropora, Pocillopora , and Porites but were not associated with adverse host response. Notably, 69–100% of fragments showing lesions were female likely reflecting the temporal reproductive life history of corals in the region. Our findings highlight endolithic organisms as major contributors to coral tissue degradation in the Arabian Peninsula. Future studies might focus on drivers of endolithic microalgal and sponge dynamics in the region and their role in coral reef health.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Understanding the petrophysical properties, seismic responses and impacts of the basalt-sediment transition in prospective sedimentary basins - Natália Famelli; John Millett; Malcolm Hole; Dougal A. Jerram; Leonardo C. de Oliveira; Evandro F. Lima; Isabela de O. Carmo; Sverre Planke; Jessica H. Pugsley; Magda Chmielewska; John A. Howell; David W. Jolley (Journal of South American Earth Sciences, 2024)

Communicating Effectively via Tele-oncology (Comskil TeleOnc): a Guide for Best Practices for Communication Skills in Virtual Cancer Care - Smita C. Banerjee; Jessica M. Staley; Frances Howell; Charlotte Malling; Aimee Moreno; Chris Kotsen; Dhwani Parikh; Patricia A. Parker (Journal of Cancer Education, 2022)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Dopamine transporter-related effects of modafinil in rhesus monkeys - Monica L. Andersen; Eileen Kessler; Kevin S. Murnane; Jessica C. McClung; Sergio Tufik; Leonard L. Howell (Psychopharmacology, 2010)

Reinstatement of extinguished amphetamine self-administration by 3,4-methylenedioxymethamphetamine (MDMA) and its enantiomers in rhesus monkeys - Jessica McClung; William Fantegrossi; Leonard L. Howell (Psychopharmacology, 2010)

Assessment of cognitive function in the heterozygous reeler mouse - Dilja D. Krueger; Jessica L. Howell; Britni F. Hebert; Peter Olausson; Jane R. Taylor; Angus C. Nairn (Psychopharmacology, 2006)